Methods for Developing Students’ Artistic Competencies through National and Traditional Art in Visual Arts Lessons - Nasulloyeva Sarvinoz Komiljon qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores methods for developing students’ artistic competencies by integrating national and traditional art into visual arts lessons. The study focuses on enhancing students’ creativity, aesthetic literacy, and understanding of national heritage. It emphasizes the use of interactive, project-based, and practical pedagogical approaches to foster students’ independent thinking and problem-solving skills. The article provides guidance for teachers on combining traditional art forms with modern educational strategies to maximize engagement and learning outcomes.